Medical radiaosotopes production: Activation cross-sections of 52Mn by the alpha-induced reaction on natural vanadium (V) - G, Damdinsuren; Kh, Tegshjargal; N, Erdene; M, Aikawa (Scientific transaction of the National University of Mongolia. Physics, 2022)
Excitation functions for α-induced reactions on natural vanadium were calculated in the energy range up to 50 MeV. The production cross sections of 52Mn will be compared to some previously published results and the TALYS (TENDL 2019) code calculations. The integral yield of 52Mn is derived from the calculated cross-sections and compared with those from other production routes.